2019
DOI: 10.1016/j.sdentj.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of Gingival Crevicular Fluid (GCF) levels of Interleukin-34 levels in periodontally healthy and in patients with chronic and aggressive periodontitis- A cross-sectional study

Abstract: Background and objectivesProinflammatory cytokines appear to have a central role in the destruction of periodontal tissues. By binding to Receptor Activator of Nuclear Factor κb (RANK) on osteoclast progenitor cells, these cytokines are locally responsible for the activation of bone resorbing osteoclasts differentiation and function. Interleukin-34 (IL-34) is a proinflammatory cytokine derived from the osteoblasts and plays an important role in osteoclastogenesis. The present study was carried out to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
(26 reference statements)
3
14
1
Order By: Relevance
“…They reported that IL-34 levels decreased after periodontal therapy performed non-surgically 38 . Opposite to our result, Parichaya et al demonstrated highest levels of IL-34 in AgP when compared with CP and periodontally healthy groups 39 .…”
Section: Discussioncontrasting
confidence: 99%
“…They reported that IL-34 levels decreased after periodontal therapy performed non-surgically 38 . Opposite to our result, Parichaya et al demonstrated highest levels of IL-34 in AgP when compared with CP and periodontally healthy groups 39 .…”
Section: Discussioncontrasting
confidence: 99%
“…Mechanistically, it has been shown that IL-34 could promote rheumatoid fibroblast-like synoviocytes (FLS) to produce IL-6, which increased the level of Th17 and further advanced RA 152 . Furthermore, IL-34 levels in gingival crevicular fluid (GCF) of patients with either chronic or aggressive periodontitis were higher than those of healthy controls 153 . Finally, IL-34 levels in the serum and synovial fluid of patients with osteoarthritis (OA) correlated with the radiographic and symptomatic severity of OA 154 .…”
Section: Csf1r Ligands and Their Differential Functions In Csf1r Signalingmentioning
confidence: 99%
“…Administration of anti-CSF1R antibodies suppresses osteoclastogenesis and bone resorption in both serum-induced inflammatory arthritis and TNFα-induced inflammatory ostelysis 122 . Imatinib, a tyrosine kinase inhibitor, prevents and treats arthritis induced by type II collagen antibody (CAIA) and collagen-induced arthritis 153 , 168 . Imatinib also suppresses CSF1R expression 169 and enhances mature osteoclast apoptosis.…”
Section: Diseases and Therapeutic Applications Of Csf1r Inhibitionmentioning
confidence: 99%
“…The synthesis of TNF-α in gum tissue can activate another cytokine, IL-1 (Pan et al 2019), which is a system of three cytokines: IL-1α, IL-1β, IL-1Ra and two receptors R 1 and R 2 (Aleхandrov 2014). It has been shown that the progression of GP in peri- odontal tissues and GCF, increases the content of IL-1 (Zyablov et al 2011;Batra et al 2019). Its increased secretion probably disrupts the mechanisms of inverse relationship that limit inflammation, leading to the formation of massive pockets in the gingival sulcus and degradation of periodontal tissue (Tsarev et al 2013).…”
Section: Discussionmentioning
confidence: 99%